2013
DOI: 10.1186/1755-8166-6-31
|View full text |Cite
|
Sign up to set email alerts
|

De novo 2.3 Mb microdeletion of 1q32.2 involving the Van der Woude Syndrome locus

Abstract: BackgroundVan der Woude syndrome is the most common among syndromes which include cleft lip and/or cleft palate as one of the presentations. It is usually caused by mutations in the interferon regulatory factor 6 (IRF6) gene.Case presentationWe previously reported on a patient with suspected deletion of the IRF6 gene. Using the Affymetrix Human SNP 6.0 Array, the interstitial deletion has been confirmed and found to be approximately 2.327–2.334 Mb within the 1q32.2 region. Although several known genes were del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 10 publications
0
15
0
1
Order By: Relevance
“…; Tan et al. ).To date, about 300 mutations causing VWS and PPS have been reported in different populations across the world (Leslie et al. ) and these include missense, nonsense, and frameshift, microdeletions and splice‐site mutations.…”
Section: Introductionmentioning
confidence: 98%
“…; Tan et al. ).To date, about 300 mutations causing VWS and PPS have been reported in different populations across the world (Leslie et al. ) and these include missense, nonsense, and frameshift, microdeletions and splice‐site mutations.…”
Section: Introductionmentioning
confidence: 98%
“…This microdeletion included the IRF6 gene, where multiple distinct point mutations and a few small deletions (ranging in size from a few base pairs up to 17 kb) account for most inherited Van der Woude syndromes, the most common autosomal dominant Mendelian malformation syndrome including oral clefts (Salahshourifar et al, ). The deletion identified by Tan et al () started in a known copy number variant site and extended into a large intron of the neighboring gene STY14 , but IRF6 remained the gene predicted to be causal in this case.…”
Section: Introductionmentioning
confidence: 83%
“…Osoegawa et al () also examined 104 nonsyndromic oral cleft patients with array‐CGH to identify two individuals with deletions: one CLP proband with a de novo 3.2 Mb deletion on chr6q25.1–25.2 and one CL proband with a 2.2 Mb deletion on chr10q26.11–26.13 transmitted from the mother (who also had a CL). Tan et al () identified a de novo deletion spanning 2.3 Mb of chr1q32 in a CLP proband with lip pits (fitting the clinical phenotype for Van der Woude syndrome, although there was no family history of oral clefts or lip pits). This microdeletion included the IRF6 gene, where multiple distinct point mutations and a few small deletions (ranging in size from a few base pairs up to 17 kb) account for most inherited Van der Woude syndromes, the most common autosomal dominant Mendelian malformation syndrome including oral clefts (Salahshourifar et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…La transmission se fait selon le mode autosomique dominant, avec une forte pénétrance (80 à 97 %) [3,4]. Le SVW est lié à une mutation des locus 1q32-q41 codant pour le gène IRF6 (Interferon Regulator Factor 6) [5][6][7], dont de multiples mutations ont été décrites [6,8]. Ce facteur est fortement impliqué dans le développement embryonnaire de la face [9].…”
Section: Observationunclassified